FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK AKUNTANSI MANAJEMEN SERTA DAMPAKNYA TERHADAP KINERJA ORGANISASI PADA SEKTOR PRIVAT DI JAKARTA (Jurnal Riset Akuntansi, 2022)
Abstract Management Accounting Practices (PAM) have an important role in companies as a basis for decision making so that company performance is effective and efficient. Management accounting practice is influenced by contingency factors, namely market competition, company owner participation, company size, environmental and technology influences. The purpose of this study was to determine the factors that influence management accounting practices and their effects on company performance. The difference with previous research is location, Management Accounting Practices (PAM) as Mediation Variables. This analysis method uses the Structural Equation Model (SEM) with Partial Least Square (PLS) as an analysis tool. Data collection is used by distributing questionnaires to company managers in Jakarta. The results showed that the owner's participation and innovative culture had an effect, while the market competition did not affect it. The factors that influence company performance are the participation of owners and PAM, while factors that do not influence it are market competition and innovative culture. Recommendations for further research are the addition of indicators, number of samples. Keywords: Market Competition Factors; Innovative Culture and Owner Participation; Management Accounting Practices; Company performance